HUBUNGAN ANTARA PARITAS, LILA, KADAR Hb DAN USIA IBU HAMIL DENGAN BERAT LAHIR BAYI - Suwarni1, Yunita; Noor, Meitria Syahadatina; Rahayu, Atikah (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2014)
The pregnant is the period was during the fetus in the womb of mother, during the pregnant is the period in which someone woman requiring various elements of nutrition that much more than is necessary in a state of ordinary. In addition to meet the needs of her own body, various the nutrients it also needed for growth and development of a fetus who was n her womb. Nutritional needs of pregnant mother during must be fulfilled to suppress the risk of weight born low (LBW). Several factors that influence the weight babies among others born baby weight, parity, hb, mother age and the upper arm circumference (LILA ) of mother. Tanah laut district  was a city with the highest number of cases LBW at South Kalimantan,  specifically 5,2 % and Pelaihari Sub-District has the highest rate of LBW in the district, which is 5.7%. The researches aims to investigate the relation between number of birth, MUAC, Hb and mother’s age with infant’s birth weight at Pelaihari Sub-District Tanah Laut City period in 2012. The researches was analytic observational approach that used cross sectional design with 267 samples. Researches instrument used secondary data. Dependent variable is birth weight infants, independent variable are number of birth, MUAC, Hb and mother’s age. Data obtained analyzed with chi square tests.The result of this researches showed that LILA (OR=22,165:p-value<0,05), HB (OR=20,907:p-value<0,05), pregnant mothers age  (OR=6,667:p-value<0,05) and parity  (p-value>0,05) that means that there was a relationship between LILA, Hb, and pregnant mothers age with heavy the baby was born. Meanwhile, there was no relationship between parity with born baby weight Key words: pregnant mother, born baby weight, number of birth,  Hb, mother’ age, LILA